2016
DOI: 10.1136/neurintsurg-2016-012304
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical thrombectomy for anterior circulation stroke: 5-year experience in a statewide service with differences in pretreatment time metrics across two hospitals sites

Abstract: Outcomes similar to randomized controlled trials are attainable in 'real-world' settings. Workflow time metrics were independent predictors of clinical outcome, and differed between the two hospitals owing to site-specific organizational differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
2
3
0
Order By: Relevance
“…Of these, 52.5% showed significant early neurological improvement (52.6% for EVT plus thrombolysis vs. 52.4% for EVT alone, p = 0.987). These results are comparable to the 59% of patients showing early neurological improvement in REVASCAT and confirm our earlier findings [7] that results from the EVT trials are achievable in a service setting.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Of these, 52.5% showed significant early neurological improvement (52.6% for EVT plus thrombolysis vs. 52.4% for EVT alone, p = 0.987). These results are comparable to the 59% of patients showing early neurological improvement in REVASCAT and confirm our earlier findings [7] that results from the EVT trials are achievable in a service setting.…”
Section: Discussionsupporting
confidence: 91%
“…We studied patients from October 2013 until April 2016. Some patients from February 2015 and prior were included in a separate state-wide audit published elsewhere [7]. Baseline information including age, sex, premorbid conditions, current medications, and initial NIHSS scores were obtained from case note review.…”
Section: Methodsmentioning
confidence: 99%
“…The rate of reperfusion with an mTICI grade ≥ 2a with the RECO device was 91%, whereas the rate of reperfusion with an mTICI grade ≥ 2b was 87%, rates in accordance with values in the lit-erature, which vary from 66.7% to 94.8%. [16][17][18][19][20] Functional independence at 90 days was attained in 63% of patients in the RECO group, again within the range described in the most optimistic studies (53%-71%). No significant difference was found in the rate of recanalization or functional independence between the RECO and Solitaire groups, confirming the efficacy of the device.…”
Section: Discussionsupporting
confidence: 78%
“…9 Our EVT cohort comprised 69% total anterior cerebral circulation strokes (OCSP TACS) and 24% partial anterior circulation strokes (OCSP PACS), which have median (interquartile range [IQR]) National Institutes of Health Stroke Severity Scores (NIHSS) of 18 (12-21) and 10 (7-15), respectively. 10 In the ESCAPE trial, the median (IQR) NIHSS for EVT-treated patients was 16 (13)(14)(15)(16)(17)(18)(19)(20). Compared with the ESCAPE trial cohort, more of our patients (86% vs 68% in ESCAPE, P ¼ .002) had occlusion of the first segment of the middle cerebral artery (M1) and fewer had occlusion of the distal internal carotid artery; otherwise, the cohorts were similar.…”
Section: Methodsmentioning
confidence: 85%
“…Multiple effectiveness studies of EVT had showed case fatality rates in the range of 20% to 27.9%. [17][18][19][20][21][22] The higher mortality rates in these studies may reflect the practice of providing comfort measures only for patients with severe deficits who do not respond to recanalization therapy. Early mortality after stroke, as seen in real-world studies, is most often attributed to the withdrawal or withholding of life-sustaining measures in light of poor prognosis and severe disabilities.…”
Section: Discussionmentioning
confidence: 99%